Beyond species counts for assessing, valuing, and conserving biodiversity: response to Wallach et al. 2019. Issue 1 (22nd December 2020) - Meyer, Ninon F. V.; Balkenhol, Niko; Dutta, Trishna; Hofman, Maarten; Meyer, Jean‐Yves; Ritchie, Euan G.; Alley, Charlotte; Beranek, Chad; Bugir, Cassandra K.; Callen, Alex; Clulow, Simon; Cove, Michael V.; et al.
Abstract : Article impact statement : Combining native and non‐native species to evaluate biodiversity is overly simplistic and may undermine the conservation of ecosystems.